2008
DOI: 10.1002/ijc.23918
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogens and risk of esophageal squamous dysplasia

Abstract: Pepsinogens are a class of endopeptidases that are secreted by the gastric epithelium and released into the circulation. Low serum pepsinogen I (PGI) and low serum pepsinogen I/pepsinogen II ratio (PGI/II ratio) are markers of gastric fundic atrophy, and have recently been shown to be associated with increased risk of esophageal squamous cell carcinoma (ESCC). We conducted the current study to test whether these markers are also associated with esophageal squamous dysplasia (ESD), the precursor lesion of ESCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…Previous studies have also found similar strong correlation coefficients between PGI and PGII,3 9 30 perhaps because both peptides are secreted by the fundic cells of the stomach. These findings are consistent with the hypothesis that the PGI/II ratio takes into account both the fact of fundic atrophy (via the PGI component) and the total secretion capacity of pepsinogens in an individual (via the PGII component).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have also found similar strong correlation coefficients between PGI and PGII,3 9 30 perhaps because both peptides are secreted by the fundic cells of the stomach. These findings are consistent with the hypothesis that the PGI/II ratio takes into account both the fact of fundic atrophy (via the PGI component) and the total secretion capacity of pepsinogens in an individual (via the PGII component).…”
Section: Discussionsupporting
confidence: 54%
“…Some previous studies suggest that chronic atrophic gastritis, defined by a low serum PGI/II ratio, is associated with risk of both ESD and ESCC (1316). A study using the same Chinese cohort that is evaluated in the current analysis also showed that lower serum PGI/II was associated with increased risk of ESD (17), but a prospective study in the same population failed to find such an association with ESCC (9). …”
Section: Introductionmentioning
confidence: 58%
“…Recent studies from Asia and Northern Europe suggest that FGA may also be associated with an increased risk for developing OSCC [15][16][17][18]. However, a large case-cohort study conducted in the People's Republic of China with over 15 years of follow-up did not support this association [19].…”
Section: Introductionmentioning
confidence: 67%
“…In 2004, Ye et al [17] first reported an association between FGA diagnosed by serology and an increased risk for OSCC in a case-control study conducted in the native Swedish population [17]. Further, case-control studies from Japan and China have reported similar data [15,16]. Bacterial overgrowth due to reduced acid secretion in patients with FGA has been proposed as a possible causal mechanism.…”
Section: Discussionmentioning
confidence: 85%